Keberadaan Capung (Odonata) Sebagai Bioindikator Di Kawasan Wisata Air Terjun Kerta Gangga Lombok Utara - Sofiyatur Rahmah; Riana Azizah; Dwika Mazraatus Sakina; Muhammad Zulhariadi (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2025)
The diversity of dragonflies (Odonata) in the Kerta Gangga Waterfall Tourist Area, North Lombok, plays an important role as a bioindicator of water quality and the surrounding ecosystem. This study aims to identify the dragonfly species found in the area and analyze the level of diversity present. The method used is the Visual Encounter Survey (VES), which allows direct observation of dragonfly species in their natural habitats. The overall ecological index calculation for dragonfly species was found to be low. The Shannon-Wiener diversity index (H’) was 1.49, classified as low, the evenness index (E) was 0.83, classified as low, the Simpson dominance index (C) was 1.20, and the Margalef richness index (D) was 1.16, which is low. Further research using more structured methods and adequate equipment is needed to provide a more accurate picture of the diversity and abundance of dragonflies in the Kerta Gangga Waterfall area.